IMPLEMENTASI KONSELING KELOMPOK DENGAN TEKNIK BIBLIOTERAPI TERHADAP PROKRASTINASI AKADEMIK SISWA SMP KELAS IX - Rizky Meiputra Nugraha; Siti Fatimah; Reza Pahlevi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
School tasks are responsibilities that must be done and completed for every student. However, there are some cases where students are late in submitting the tasks, while the others do not even submit them at all. The behavior of delaying the responsibility is called procrastination, and if the responsibility is in academic things, then it is called academic procrastination. Academic procrastination behavior can have an impact on students' grades. Guidance and counseling teachers can help counselees in solving academic procrastination problems by using group counseling with bibliotherapy techniques. The subjects of this study are two students who have procrastination behavior and one guidance and counseling teacher. This study use qualitative research method with descriptive approach.  This study aims to determine the implementation of group counseling using bibliotherapy techniques on academic procrastination of ninth-grade junior high school students. Guidance and counseling teachers can use group counseling with bibliotherapy and the I SOLVE strategy to reduce academic procrastination behavior for ninth-grade junior high school students. Keywords: : Group Counseling, Bibliotherapy, Academic Procrastination